The Influence of Statin Therapy on Markers of Endothelial Dysfunction, Endocan and Endoglin, in Postmenopausal Women—A Prospective Study - Dunja Šojat; Marko Pirić; Maja Lukić; Vesna Horvat; Mario Šafer; Ivan Feldi; Tatjana Bačun; Aleksandar Kibel (Biomedicines, 2026)
Background: Postmenopausal women experience an increased risk of cardiovascular diseases due to estrogen deficiency, which induces endothelial dysfunction. Statins primarily lower cardiovascular risk by altering lipid profiles, but they also exert non-lipid-modifying, pleiotropic effects on the vascular endothelium. This prospective observational study was aimed to evaluate and compare the impact of atorvastatin and rosuvastatin on plasma markers of endothelial dysfunction, endocan and endoglin, in postmenopausal women undergoing primary cardiovascular prevention. Methods: A total of 128 postmenopausal Croatian women (aged 45–70 years) with dyslipidemia were prospectively enrolled and assigned to two treatment groups receiving either atorvastatin or rosuvastatin therapy based on primary care clinical management. Cardiovascular risk was evaluated using the SCORE2 algorithm, and statin doses were titrated up to 16 weeks until target LDL-C values were achieved. Plasma concentrations of endocan and endoglin, alongside lipid profiles, were quantified via ELISA and laboratory analyses before and after the treatment period. Results: Atorvastatin and rosuvastatin therapies significantly decreased plasma concentrations of both endocan and endoglin (p < 0.001 for both groups). No statistically significant differences in the absolute changes in these biomarkers were observed between therapy groups. The reduction in endocan and endoglin levels occurred independently of whether the participants achieved their clinical target LDL-C values. While statin-induced reduction in endoglin was directly driven by the extent of LDL-C lowering, the decrease in endocan occurred independently of lipid changes, with both biomarker reductions being greatest in women with higher baseline levels regardless of statin type or dose. ROC curve analysis demonstrated that neither biomarker had significant clinical discriminatory ability to predict the attainment of target LDL-C levels. Conclusions: Atorvastatin and rosuvastatin treatment was associated with significant reductions in plasma endocan and endoglin concentrations in postmenopausal women receiving primary cardiovascular prevention.